“THE INFLUENCE OF PETERSBURG IN THE WORKS OF F.M. DOSTOEVSKY: LITERARY SPACE AND PSYCHO-GEOGRAPHY OF THE CITY” - Adilova Tursunoy Kadirovna (Ecominds Press, 2025)
This article examines the role of Saint Petersburg in the literary world of Fyodor Dostoevsky. The city appears not merely as a setting, but as an active agent that influences the psychology of characters, the development of events, and the philosophical foundation of the narratives. The study analyzes the structure of urban space, its symbolic significance, and the dual nature of Petersburg as both a civilizational project and a source of alienation. Special attention is given to the novels Crime and Punishment, Poor Folk, The Idiot, and Demons. The article concludes that Saint Petersburg plays a central role in shaping Dostoevsky’s aesthetics and worldview.